Fortnightly changes in water transport direction across the mouth of a narrow estuary - Garel, Erwan (2018)
This research investigates the dynamics of the axial tidal flow and residual circulation at the lower Guadiana Estuary, south Portugal, a narrow mesotidal estuary with low freshwater inputs. Current data were collected near the deepest part of the channel for 21 months and across the channel during two (spring and neap) tidal cycles. Results indicate that at the deep channel, depth-averaged currents are stronger and longer during the ebb at spring and during the flood at neap, resulting in opposite water transport directions at a fortnightly time scale. The net water transport across the entire channel is up-estuary at spring and down-estuary at neap, i.e., opposite to the one at the deep channel. At spring tide, when the estuary is considered to be well mixed, the observed pattern of circulation (outflow in the deep channel, inflow over the shoals) results from the combination of the Stokes transport and compensating return flow, which varies laterally with the bathymetry. At neap tide (in particular for those of lowest amplitude each month), inflows at the deep channel are consistently associated with the development of gravitational circulation. Comparisons with previous studies suggest that the baroclinic pressure gradient (rather than internal tidal asymmetries) is the main driver of the residual water transport. Our observations also indicate that the flushing out of the water accumulated up-estuary (at spring) may also produce strong unidirectional barotropic outflow across the entire channel around neap tide.